Anisotropic cellular structures from semi‐crystalline polymer templates. Issue 23 (5th November 2020) - Kanbargi, Nihal; van Erp, Marco J.; Lesser, Alan J.
Abstract: We report an investigation to determine the effect of an anisotropic semi‐crystalline template on the resulting cell morphology of microcellular polymeric foams generated in these materials. Poly(ethylene terephthalate) (PET)‐polystyrene (PS) composite foams are prepared by using supercritical carbon dioxide (scCO2 ) not only as a foaming agent but also as a transport medium of styrene and initiator into a biaxially‐oriented PET templating film. The composite foam so obtained demonstrates a highly interpenetrating network verified by a single Tg of 98°C. Substrate orientation is observed not to dictate the cell formation; however highly anisotropic swelling and a shape‐templating phenomenon is observed, with the most significant dimension change in the thickness of the film. Introducing confinement in the direction of maximum dimension change is found to introduce a highly anisotropic lamellar cell architecture. Abstract : The introduction of cellular anisotropy in polymeric foams can potentially open avenues for fine‐tuning and optimization of mechanical properties, energy absorption, and thermal insulation that would be difficult to achieve in their isotropic analogues. This study focuses on whether a biaxially oriented, semi‐crystalline polyethylene terephthalate (PET) film substrate can "template" cellular anisotropy in supercritical carbon dioxide (ScCO2 ) assisted synthesis of biphasic composite foams of PET with polystyrene (PS).